Biofilms in Full-Scale Drinking Water Ozone Contactors Contribute Viable Bacteria to Ozonated Water - Kotlarz, Nadine; Rockey, Nicole; Olson, Terese M; Haig, Sarah-Jane; Sanford, Larry; LiPuma, John J; Raskin, Lutgarde (Environmental science & technology, 2018)
Concentrations of viable microbial cells were monitored using culture-based and culture-independent methods across multichamber ozone contactors in a full-scale drinking water treatment plant. Membrane-intact and culturable cell concentrations in ozone contactor effluents ranged from 1200 to 3750 cells/mL and from 200 to 3850 colony forming units/mL, respectively. Viable cell concentrations decreased significantly in the first ozone contact chamber, but rose, even as ozone exposure increased, in subsequent chambers. Our results implicate microbial detachment from biofilms on contactor surfaces, and from biomass present within lime softening sediments in a hydraulic dead zone, as a possible reason for increasing cell concentrations in water samples from sequential ozone chambers. Biofilm community structures on baffle walls upstream and downstream from the dead zone were significantly different from each other (p = 0.017). The biofilms downstream of the dead zone contained a significantly (p = 0.036) higher relative abundance of bacteria of the genera Mycobacterium and Legionella than the upstream biofilms. These results have important implications as the effluent from ozone contactors is often treated further in biologically active filters and bacteria in ozonated water continuously seed filter microbial communities.